DEVELOPMENT AND VALIDATION OF HPTLC METHOD FOR ESTIMATION OF VOGLIBOSE IN PHARMACEUTICAL DOSAGE FORMS - Shinde, Charushila C.; Chopade, Shakuntala; Dhaneshwar, Suneela S. (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: This paper describes a new, simple, precise, accurate and specific HPTLC method for estimation of voglibose as a bulk drug and in tablet dosage forms. Methods: Chromatographic separation of the drug was performed on aluminum plates pre-coated with silica gel 60 F254 as the stationary phase and a mobile phase comprising of toluene: ethyl acetate: methanol: 30% ammonia 5:4:1.5:0.2 (v/v/v/v). Densitometric quantification of voglibose was carried out at 292 nm. Voglibose was detected satisfactorily with a Rf value 0.26. Results: The accuracy and reliability of the method was assessed by evaluation of linearity (0.2-1.2 Âµg/spot), precision (intra-day RSD 0.6-0.9% and inter-day RSD 0.20-0.25%), accuracy (97.32-102.46%) and specificity according to ICH guidelines. Conclusion: The proposed HPTLC method is less expensive, simpler, rapid and more flexible than the reported RP-HPLC method for routine analysis of voglibose in bulk and tablet dosage forms. Â